A Practical Approach to the Care of Adolescents and Young Adults with Cancer (Springer International Publishing, 2018)
This book discusses the most important practical aspects involved in providing multidisciplinary Adolescent and Young Adult (AYA) services for cancer patients. It draws on international experience in several continents of establishing and running such services and provides a contemporary, practical approach to AYA care based on accumulated experience. It is of interest to those establishing or seeking to improve AYA services as well as those already caring for AYA cance patients. Among topics discussed are incidence trends and treatment pathways, access to clinical trials for adolescents, transition from pediatric to adult services, psychological support and social care as well as survivorship and fertility. This book is of value of those establishing new services, those developing an existing service and those whose work includes the care of AYA patients. It is an important companion for pediatricians, oncologists as well as o ther medical, nursing and allied health professionals caring for Adolescents and Yound Adults with cancer.